(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
The type species of the spiriferinide genus Histosyrinx Termier & Termier (Brachiopoda), namely Histosyrinx vautrini Termier & Termier, is re-investigated in detail on the basis of its type material from the Tournaisian Marar Formation (Serdeles area, Murzuq Basin, Libya), including additional specimens from the same region, and from the Tournaisian of Algeria (Reggane Basin). The internal morphology of the ventral valve of Histosyrinx vautrini is particularly variable, notably concerning the development of the septal pillow, the subdelthyrial plate and the median septum. Histosyrinx can be easily distinguished from the genus Septosyringothyris Vandercammen by the absence of a true delthyrial plate and the lesser development of the median septum. Histosyrinx is also close to Syringopleura Schuchert, which is generally considered as a synonym of Syringothyris Winchell, by its ventral internal features (e.g. development of a septal pillow), but the dorsal internal morphology of the type species of Schuchert’s genus remains unknown. Thus, the relationships between both genera need to be investigated further. Specimens from the southern margin of the Tindouf Basin (Algeria), previously identified as Septosyringothyridinae? gen. indet. by Legrand-Blain in the 1970s, are fully illustrated here for the first time and referred to an unidentified genus of the subfamily Permasyrinxinae on the basis of the absence of syrinx.